2022
DOI: 10.13075/ijomeh.1896.01862
|View full text |Cite
|
Sign up to set email alerts
|

Physiological workload of workers employed during motor-manual timber harvesting in young alder stands in different seasons

Abstract: Objectives: This study examined the physiological strain experienced by workers employed in motor-manual timber harvesting performed in winter and summer, and the applicability of heart rate indices for estimating energy expenditure. Material and Methods: The heart rates (HR) of 2 teams consisting of 2 persons working simultaneously during felling and forwarding, in both winter and summer, were measured. Heart rate at work (HR work ), resting heart rate (HR rest ), relative heart rate (%HRR), ratio of working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The results of the association between heart rate and metabolic rate were in accordance with a previous formula [20]. Several studies have reported small sample sizes in actual forestry fields (5-13 participants) [10][11][12][13]. A low risk of a statistical type 2 error due to small sample size, which indicates a small measurement error in correlation, may be a strength for implementing the main study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the association between heart rate and metabolic rate were in accordance with a previous formula [20]. Several studies have reported small sample sizes in actual forestry fields (5-13 participants) [10][11][12][13]. A low risk of a statistical type 2 error due to small sample size, which indicates a small measurement error in correlation, may be a strength for implementing the main study.…”
Section: Discussionsupporting
confidence: 85%
“…Heart rate (HR) monitoring is widely used to estimate the workload. Several studies have measured the workload of forestry workers using HR monitors in the field [9][10][11][12][13][14]. They reported a single task or operation, such as afforestation, pruning, felling, or cable work, and used the crude or HR relative to the maximal or submaximal HR.…”
Section: Introductionmentioning
confidence: 99%
“…A baseline work demand as a predictor of an health outcome, assumes that physical work demands do not change during the follow up period. However, this is often not the case as people can change jobs and/or their work tasks can change in intensity during the course of a career (Åkerstedt et al 2019 ), or across seasons (Grzywiński et al 2022 ), workweeks or days (Sandlund et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, chainsaw use has its drawbacks, including noise, vibrations, physical strain, exhaust gases, and airborne wood dust [10]. Several researchers have examined the problems associated with noise [11,12,13], vibrations [14,15,16], physical strain [17,18,19], as well as the determination of carbon monoxide [20,21], and exhaust emissions [22,23,24].…”
Section: Introductionmentioning
confidence: 99%